Structural, Optical, Photoluminescence Studies onto the Incorporation of Copper in Tin Oxide Nanostructure and Evaluation of their Antimicrobial Property - Rathinabala, R.; Selvi, R. Thamiz (Asian Journal of Chemistry, 2020)
Biosynthesis of undoped and copper doped tin oxide (SnO2) nanoparticles were carried out using Canna indica leaf extracts as reducing agents. The as-synthesized nanoparticles were characterized using the powder X-ray diffraction (PXRD), scanning electron microscope (SEM), Fourier transformed infrared spectroscopy (FTIR), UV-visible spectroscopy and photoluminescence (PL). Antimicrobial behaviour of the synthesized nanoparticles was examined. The XRD studies revealed that the rutile structure for both undoped and copper doped SnO2 nanoparticles, with the absence of secondary phases. The SEM micrographs clearly showed the formation of well-defined spherical particles with no impure phases. The optical absorption studies explained that the variation of band gap with particle size. The photoluminescent spectra showed an emission peaks at 390, 520 and 790 nm, which are ascribed to the structural defects due to the oxygen vacancy. The antibacterial investigation suggested a better antibacterial activity for Staphylococcus aureus against Escherialia coli bacterial strains.